RELATIONSHIP BETWEEN CARDIAC AUTONOMIC NEUROPATHY AND PLASMA HOMOCYSTEINE LEVEL IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Kyaw, Theingi; Latt, Chan Nyein; Min, Phyo Maung Maung; Zaw, Myo Thiha; Naing, Thet (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Cardiac Autonomic Neuropathy is one of the diabetic complications that can lead to silent myocardial infarction, arrhythmia, and sudden death. Hyperhomocysteinemia was associated with macro- and microvascular complications of diabetes mellitus, including cardiac autonomic neuropathy. METHODOLOGY The study aimed to investigate the relationship between cardiac autonomic neuropathy and plasma homocysteine levels in patients with type 2 diabetes mellitus. Ninety-six patients with type 2 diabetes mellitus were included in this cross-sectional analytical study. Plasma homocysteine was measured by Cobas C311 analyzer. Diagnosis of cardiac autonomic neuropathy was based on Ewing’s test and categorized into early CAN, severe CAN, and patients without CAN by using Bellavere’s scoring system. RESULTS Among the patients, the majority (71.9%) did not have cardiac autonomic neuropathy (score <2). In those with cardiac autonomic neuropathy, early autonomic neuropathy (scores 2-4) was found among 24% of patients. Severe autonomic neuropathy (scores 5-10) was noted among 4.1% of patients. The mean ± SD level of plasma homocysteine was 14.08 ± 5.29 µmol/L. The range was from 4.24 to 28.21 µmol/L. The mean ± SD level of plasma homocysteine level of patients without CAN was 11.84 ± 3.59 μmol/L. Among patients with CAN, the mean ± SD level of plasma homocysteine level of patients with early CAN was 19.88 ± 4.76 μmol/L while that of patients with severe CAN was 19.42 ± 4.13 μmol/L. Post hoc comparison using the Tukey HSD test indicated that the mean values of plasma homocysteine levels for early CAN and severe CAN patients were significantly different from the mean values of plasma homocysteine levels for patients without CAN, with p <0.001 and 0.001 respectively. In this study, older patients were more likely to develop CAN. CAN was detected more frequently among male patients. Smoking status, hypertension, and HbA1c level were not associated with CAN. Patients suffering from DM for more than 5 years were 2.75 times more likely to have CAN than patients with DM for less than 5 years. This finding was statistically significant with p = 0.034. CONCLUSION In this study, there was a relationship between cardiac autonomic neuropathy and plasma homocysteine level in patients with type 2 diabetes mellitus. To reduce the cardiovascular complication of cardiac autonomic neuropathy, early CAN diagnosis is useful to establish an adequate therapeutical strategy for glycaemic control and personalized treatment.